Pelatihan Digital Marketing Melalui Instragram, Canva dan Whatsapps Business Bagi Ibu Rumah Tangga Pelaku Usaha Kuliner - Rezeki, Syailendra Reza Irwansyah Rezeki; Wahdiniawati , Siti Annisa Wahdiniawati; Octiva , Cut Susan Octiva; Yuliana, Rachma Yuliana; Feriyadin, Feriyadin (Jurnal Pengabdian Kepada Masyarakat Kalam, 2024)
Digital transformation has become a strategic necessity in the development of small businesses, including home-based enterprises run by housewives. However, many home-based culinary entrepreneurs lack skills in digital marketing. This community service activity aims to enhance digital marketing capacity for housewives involved in culinary businesses in Lenteng Agung, South Jakarta. The training focuses on three main platforms that are easily accessible and user-friendly: Instagram, Canva, and WhatsApp Business. The methods employed include initial observation, preparation of training modules, face-to-face training, hands-on practice, as well as mentoring and evaluation. The results of the activity indicate a significant improvement in participants' abilities to create engaging promotional content, understand promotional functions and features on Instagram, and use WhatsApp Business proficiently. This is reflected in the pre-test and post-test results, which show an average score increase of 45–55%, particularly in the categories of promotional content creation, visual branding, and social media utilization. The evaluation of the activity also demonstrates a very high level of participant satisfaction, with an average score above 4.5 in terms of material relevance, participant engagement, and facilitator performance. This improvement indicates the success of the practice-based training method that is directly oriented towards participants' needs. It is hoped that this training can serve as a foundational step in the economic empowerment of families based on digital technology, while also encouraging housewives to be more confident in utilizing social media as an effective and sustainable promotional tool.